In vitro functional analysis of 24 novel CYP2C19 variants recently found in the Chinese Han population. (2nd November 2015) - Dai, Da-Peng; Hu, Li-Ming; Geng, Pei-Wu; Wang, Shuang-Hu; Cai, Jie; Hu, Guo-Xin; Cai, Jian-Ping
Abstract: 1. CYP2C19 is a highly polymorphic enzyme responsible for the metabolism of a wide range of clinical drugs. Alterations to the CYP2C19 gene contribute to the variability of CYP2C19 enzyme activity, which causes pharmacokinetics and drug efficacies to vary and adverse drug reactions to occur in different persons. Recently, we identified 24 novel CYP2C19 allelic variants in the Chinese Han population. The purpose of present study is to assess the impact of these newly found nucleotide mutations on the enzymatic activity of the CYP2C19 protein. 2. Dual-expression vectors were constructed and transiently transfected into 293FT cells. Forty-eight hours after transfection, cells were re-suspended and incubated with two typical probe substrates, omeprazole and S- mephenytoin, to determine the activities of each variant relative to the wild-type protein. 3. Immunoblotting results showed that the protein expression levels of the CYP2C19 variants were diverse. Enzymatic ability analysis showed that the variant 35FS exhibited no functional activity, and most of the other variants showed significantly decreased metabolic activities toward both omeprazole and S- mephenytoin compared with wild-type. 4. These findings greatly enrich the knowledge of biological effects of these newly found CYP2C19 mutations and aid the application of this knowledge to future individualized drug therapy in clinic.